Tensile cracking behavior of oxide scale in hot-rolled steel - WANG Shang; YANG Quan; REN Yun-he; WANG Xiao-chen; SHAN Zhong-de (工程科学学报)
The microstructure, structure, and cracking behavior of Q235-A strip iron oxide skin were studied using X-ray diffraction (XRD), scanning electron microscopy (SEM), and a universal tensile testing machine. The results show that the composition of the iron oxide mainly consists of Fe3O4, Fe2O3, and Fe, together with small amount of FeO, the oxide layer has the same thickness all over, about 10 μm, the structure is dense, and the matrix is better connected. The tensile experiments show that with increasing strain, the increase in the number of cracks is at first slow, then fast, then slow again. When the strain reaches 0.05%, its iron oxide skin begins to crack; the number of cracks increases with increasing strain in the range 0.08% -0.10%. When the strain exceeds 0.10%, the crack number increases slowly, and when the strain exceeds 0.15%, the number of cracks stops grow.